Analisis Faktor Keberhasilan Pengobatan Penderita TB-Paru Di RSU Imelda Pekerja Indonesia Tahun 2023 - Carryn Carryn; Arifah Devi Fitriani; Nuraini Nuraini (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
To achieve recovery, TB sufferers must have self-confidence about how serious the condition and symptoms of the disease are and the impact on daily life. So that TB sufferers are able to carry out treatment for a long period of time and TB sufferers have the confidence to recover from the disease. The aim to be achieved in this research is to analyze the success factors for treatment of pulmonary TB sufferers at the Imelda Workers Indonesian RSU in 2023. This type of research uses a descriptive analytical survey with a cross sectional design. The population in this study were all category I pulmonary tuberculosis patients who visited the Imelda Workers Indonesian Hospital from January to September 2023, a total of 118 people were sampled using the accidental sampling method while the sample was 91 people. Data analysis was carried out using univariate, bivariate and multivariate analysis. Based on the results of the chi-square test, it is known that patient success influences knowledge, family support, supervision of taking medication and support from health workers with a value of p = 0.001, meaning that there is an influence of knowledge, family support, supervision of taking medication and support from health workers on the success of TB treatment. Lungs. From the results of the multivariate analysis, it is known that the most influential variable in this study is the medication monitoring variable with an OR value of 15.104. The conclusion in this study is that medication-taking supervisors are the dominant factor influencing the success of pulmonary TB treatment at the Indonesian Imelda Workers RSU. The advice given is in the form of instructions for using a daily insulated medicine box, using a smart calendar during treatment which is brought to you every time you come for treatment and in the current digital era, using the mHealth application is also very helpful in providing TB information notifications and reminders to take medication regularly for sufferers and PMOs.